The impact of COVID-19 pandemic on emotional and behavioral problems of children with autism spectrum disorder and developmental delay aged 1–6 years in China - Zhao, Yanan; Luo, Yanan; Zhang, Rong; Zheng, Xiaoying (Frontiers in Psychiatry, 2023)
Introduction The COVID-19 pandemic outbreak have caused increased levels of emotional and behavioral problems, particularly among people with pre-existing mental health conditions. Young individuals with autism spectrum disorders (ASD) and developmental delay (DD) are particularly at risk due to their vulnerability. The purpose of this study was to look into the different effects of the COVID-19 pandemic on 1–6-year-old children with ASD and DD. Methods Parents and guardians of children with ASD completed an online survey that included questions about their children’s socio-demographics characteristics, the effects of the COVID-19 outbreak on their health, and what they needed in order to deal with the conditions of the pandemic. Results This study compared 4,138 children with ASD to 711 children with DD. Children with ASD had a higher risk of having more emotional and behavioral problems than children with DD (OR 1.38, 95% CI 1.12–1.70). Compared to parent-oriented rehabilitation at home, discontinuing rehabilitation had a higher likelihood of negative emotional and behavioral change (OR 1.67, 95% CI 1.41–1.98). Having teachers’ online support had a higher likelihood of negative emotional and behavioral change for ASD children (OR 1.26, 95% CI 1.03–1.54). Conclusions This article provided evidence that children with developmental disabilities, particularly ASD, were at risk for a variety of challenges to their emotional functioning during the COVID-19 period, and that online support was not an ideal way for children with ASD to receive effective educational intervention in China.